A novel high throughput screening platform reveals an optimised cytokine formulation for human hematopoietic progenitor cell expansion - Tarunina,M; Hernandez,D; Kronsteiner-Dobramysl,B; Pratt,P; Watson,T; Hua,P; Gullo,F; Van,der Garde M; Zhang,Y; Hook,L; Choo,Y; Watt,S (Stem Cells and Development, 2016)
The main limitations of hematopoietic cord blood (CB) transplantation, viz. low cell dosage and delayed reconstitution, can be overcome by ex-vivo expansion. CB expansion under conventional culture causes the rapid cell differentiation and depletion of hematopoietic stem/progenitor cells (HSPC) responsible for engraftment. Here, we use combinatorial cell culture technology (CombiCult®) to identify media formulations that promote CD133+ CB HSPC proliferation while maintaining their phenotypic characteristics. We employed second generation CombiCult® screens that use electro-spraying technology to encapsulate CB cells in alginate beads. Our results suggest that, not only the combination, but also the order of addition of individual components has a profound influence on expansion of specific HSPC populations. Top protocols identified by the CombiCult® screen were used to culture human CD133+ CB HSPCs on nanofiber scaffolds and validate the expansion of the phenotypically defined CD34+CD38lo/-CD45RA-CD90+CD49f+ population of hematopoietic stem cells and their differentiation into defined progeny.